Motivasi Kerja Aparatur dalam Penyelenggaraan Pemerintahan di Kecamatan Belopa - Riska Amalia Armin; Muhammad Tamar; Andi Lukman Irwan (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2009)
Abstract: This study aims to determine the efforts made in improving the motivation of personnel working in the district Belopa and know the factors that influence the motivation to work in the administration of government officials in the district Belopa. Type of study is a explanatif. form the study is a form of field research by using survey method. Data collection techniques performed using the technique literature study, observation, interviews, quisioner and search data online. Data were collected from various sources to obtain sufficient data. The results of this study indicate that efforts are made to improve the motivation of personnel working in governance at the district Belopa is "good" with the average value of 3,00 while the factors that influence the motivation to work is also included in the category of "good" with the average value of 3,00. Then the hypothesis put forward acceptable to the motivation to work towards the running of influential officials in the district and work motivation apparatus Belopa effect on the factors that influence. Keywords: motivation, influence, opparatus, work, governmentAbstrak: Penelitian ini bertujuan untuk mengetahui pengaruh motivasi kerja aparatur dalam penyelenggaraan pemerintahan di Kecamatan Belopa serta mengetahui pengaruh motivasi kerja aparatur  terhadap faktor-faktor yang mempengaruhinya. Tipe penelitian yang digunakan adalah explanatif. Bentuk penelitian yang digunakan adalah bentuk penelitian lapangan dengan  menggunakan metode survey. Teknik pengumpulan data dilakukan menggunakan teknik studi pustaka, observasi, wawancara, kuisioner dan penelusuran data on line. Data dikumpulkan dari berbagai sumber hingga didapatkan data yang cukup. Hasil penelitian ini menunjukkan bahwa pengaruh motivasi kerja aparatur dalam penyelenggaraan pemerintahan di Kecamatan Belopa adalah “Baik” dengan nilai rata-rata 3,00 sedangkan pengaruh motivasi kerja aparatur terhadap faktor-faktor yang mempengaruhinya juga termasuk dalam kategori “Baik” dengan nilai rata-rata 3,00. Maka hipotesa yang dikemukakan dapat diterima yakni motivasi kerja aparatur berpengaruh terhadap penyelenggaraan pemerintahan di Kecamatan Belopa dan Motivasi kerja aparatur berpengaruh terhadap faktor-faktor yang mempengaruhinya.Kata kunci: motivasi, pengaruh, aparatur, kinerja, pemerintahan